The Effectiveness Of Wattpad Online Reading Application Into Students’ English Reading Skill By Using Structure-Proposition-Evaluation (SPE) Method To 8th Students In SMP HKBP SIDORAME - Yessica Indah Sinaga; Yessy Octaviana; Febrika Dwi Lestari; Harsakso Sinurat (Innovative: Journal Of Social Science Research, 2023)
The purpose of this research is to know the effect of Wattpad online reading application by using SPE method on students’ into English reading skill. This research conducted by using quasi experimental research. The subject of this research is class of 8th SMP HKBP SIDORAME which consists of 20 students. The class was divided in two groups, namely experimental class which had been taught by Wattpad application with SPE method and control class which had been taught by conventional class The data were analyzed by using t-test formula .The finding indicates that the value of t-test exceeds the value of t-table (5,87 > 2,101), at the level of significant p = 0,05 and the degree freedom df = 18. The finding implies that the alternative hypothesis is accepted. In order words, there is a significant effect of using Wattpad online reading application into students’ English reading skill by using Structure – Proposition - Evaluation (SPE) method.”